Effectiveness of bio-rational insecticides against pod borer of yard long bean and their effect on natural enemies (Annals of Bangladesh Agriculture, 2025)
Pod borer, Euchrysops cnejus (Fab.) is the most destructive pest of yard long bean. A study was conducted during March to July 2022 in the experimental field of the Department of Entomology, Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur, Bangladesh to evaluate the effectiveness of some bio-rational insecticides against pod borer of yard long bean. The experiment was conducted following Randomized Complete Block Design (RCBD) with 3 replications. The treatments were Vermitec 1.8 EC (Abamectin) @1.0 ml/L, Tracer 45 SC (Spinosad) @ 0.4 g/L, Bio-Action 1.5 SL (Matrine) @ 1.5 ml/L of water, Ecomec 1.8 EC (Azadiractin) @ 1.5 ml/L and Phytoclean (Potassium salt of fatty acid 40%) @1.5 ml/L of water were applied thrice at 15 days interval along with an untreated control for comparison. The tested insecticides had no adverse effects on lady bird beetle, syrphid fly, black ant and spider. The study revealed that, the lowest rate of pod infestation at 3 and 7 days after each spray as well as the highest marketable yield (10.7 MT/ha) and marginal benefit cost ratio (7.7) were recorded with management approach comprising Tracer 45 SC (Spinosad) @ 0.4 g/L of water at 15 days interval which might be recommended for suppressing pod borer of yard long bean. Ann. Bangladesh Agric. 28(1): 39-47